2012
DOI: 10.1021/ic3007469
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical and Photoredox Characteristics of a Novel Tricarbonyl Rhenium(I) Complex Having an Arylborane-Appended Aromatic Diimine Ligand

Abstract: We report the synthesis and photophysical/photoredox characteristics of a novel tricarbonyl rhenium(I) complex having a (dimesityl)boryldurylethynyl (DBDE) group at the 4-position of a 1,10-phenanthroline (phen) ligand, [Re(CO)(3)(4-DBDE-phen)Br] (ReB). ReB in tetrahydrofuran at 298 K showed the metal-to-ligand charge transfer (MLCT) emission at around 681 nm with the lifetime (τ(em)) of 900 ns. The relatively long emission lifetime of ReB compared with that of [Re(CO)(3)(phen)Br] (RePhen, τ(em) = 390 ns) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 100 publications
(50 reference statements)
5
24
0
Order By: Relevance
“…ReBbpy also showed the third reduction wave at -1.80 V. Since the third reduction wave similar to that of ReBbpy has been observed for ReBphen (see Table 1) [33], we can safely ascribe the potential to the reduction of the boron atom in the DBDE group. Such electrochemical characteristics of ReBbpy should reflect on the excited-state characteristics of the complex as described in the following sections.…”
Section: Cyclic and Differential Pulse Voltammogramssupporting
confidence: 68%
See 4 more Smart Citations
“…ReBbpy also showed the third reduction wave at -1.80 V. Since the third reduction wave similar to that of ReBbpy has been observed for ReBphen (see Table 1) [33], we can safely ascribe the potential to the reduction of the boron atom in the DBDE group. Such electrochemical characteristics of ReBbpy should reflect on the excited-state characteristics of the complex as described in the following sections.…”
Section: Cyclic and Differential Pulse Voltammogramssupporting
confidence: 68%
“…The second irreversible reduction wave (E(Re 0/-I ), dissociative reduction of the Br ligand) of ReBbpy was observed at -1.45 V and was also shifted to the positive direction by 250 mV compared with that of Rebpy. These positive shifts of the reduction potentials of ReBbpy can be Table 1 includes the redox potentials of ReBphen and Rephen reported earlier [33] to discuss the diimine ligand effects on the redox behaviors of the complexes. These four complexes showed comparable oxidation potentials at around E(Re II/I ) = + 1.41-1.45 V, and this demonstrated that the HOMO energies of the complexes were very similar with one another as described above.…”
Section: Cyclic and Differential Pulse Voltammogramsmentioning
confidence: 88%
See 3 more Smart Citations